2002
DOI: 10.1046/j.1472-765x.2002.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the effects of herbicides on the growth of rhizobia

Abstract: Aims:To study the possible adverse effect of herbicides on nodulation and nitrogen fixation in legumes by affecting the nitrogen-fixing rhizobia. Methods and Results: Experiments were conducted to study the effect of four herbicides (terbutryn/terbuthylazine, trietazine/simazine, prometryn and bentazone) on the growth of nitrogen-fixing pea rhizobia (Rhizobium leguminosarum) in vitro by measuring optical density. Terbutryn/terbuthylazine, trietazine/simazine and prometryn had an adverse effect on the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 16 publications
5
27
0
Order By: Relevance
“…In dual application of pre followed by post emergence herbicide, the highest Rhizobium population was noticed in pendimethalin (PRE) + phenaxoprop ethyl (POE) applied treatment (3.14 x 10 4 cfu per gram of soil) and lowest count of Rhizobium was found in pendimethalin + oxyfluorfen treated plot (2.98 x 10 4 cfu per gram of soil). Similar results reported by Singh and Wright (2002) that the adverse effect of herbicides on nodulation and nitrogen fixation in legumes by affecting the nitrogen-fixing Rhizobia (Rhizobium leguminosarum population). Whereas, Felipe et al, (1987) suggested that, the direct effects of herbicides on the plant, decreased the number of nitrogen-fixing bacteroids.…”
Section: Resultssupporting
confidence: 87%
“…In dual application of pre followed by post emergence herbicide, the highest Rhizobium population was noticed in pendimethalin (PRE) + phenaxoprop ethyl (POE) applied treatment (3.14 x 10 4 cfu per gram of soil) and lowest count of Rhizobium was found in pendimethalin + oxyfluorfen treated plot (2.98 x 10 4 cfu per gram of soil). Similar results reported by Singh and Wright (2002) that the adverse effect of herbicides on nodulation and nitrogen fixation in legumes by affecting the nitrogen-fixing Rhizobia (Rhizobium leguminosarum population). Whereas, Felipe et al, (1987) suggested that, the direct effects of herbicides on the plant, decreased the number of nitrogen-fixing bacteroids.…”
Section: Resultssupporting
confidence: 87%
“…Herbicides may decrease nodulation and nitrogenase activity not only by influencing plant growth but also by affecting rhizobia. Though the herbicides used in the present studies did not adversely affect the growth of rhizobia in vitro at the recommended field application rates (Singh and Wright, 2002), other herbicides need to be tested for their possible adverse effects on rhizobia.…”
Section: Practical Problems Possible Solutions and Future Direction mentioning
confidence: 91%
“…While comparing the sum of mean values of two dose rates of each herbicide independently, the order of toxicity on total biomass production increased in the following order: sulfosulfuron < isoproturon < atrazine < metribuzin. Evaluation of the herbicide effects on legume cultivation is complicated because herbicide may not only affect the rhizobia in the free living state in soil and within root tissues but also affect plant growth (Singh and Wright, 2002). In the present study, the trend observed, suggests that the lower rate (200 µg.a.i.kg -1 ) in general, had little effect on the growth of the test plants suggesting that herbicides at this rate persisted in soil for only a short duration, after which the viable cells of Bradyrhizobium recovered and multiplied rapidly leading thereby to the establishment of an effective symbiosis with the host plant.…”
Section: Micmentioning
confidence: 99%